Correlation and path analysis studies in onion (Allium cepa) genotypes - YOGITA; KUMAR, RAMESH; SINGH, DAVINDER; YADAV, KALPANA; SRISHTI; ROHILA, ANIL KUMAR; KUMAR, AJAY; TYAGI, NIDHI; KUMAR, AMIT (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at the experimental farm of the Department of Vegetable Sciences, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh during the winter (rabi) season of 2019–20 and 2020–21 to study the genetic variability, correlation and path studies in 30 different genotypes of the onion (Allium cepa L.) crop. All genotypes reflected a wide and significant spectrum of variability for all the traits under study. Genotypes UHF-ONI-13, UHF-ONI-15 and UHF-ONI-16 outperformed other genotypes in terms of yield and other critical horticultural characteristics. The magnitude of phenotypic coefficient of variation was higher than the genotypic coefficient of variation for all the characters. The phenotypic and genotypic coefficients of variability were high for doubles/deformed bulbs, moderate for leaf length, plant height, average bulb weight, bulb yield per plot and per hectare. High heritability along with high to moderate genetic gain was observed for doubles/deformed bulbs, leaf length, plant height, average bulb weight, bulb yield per plot and bulb yield per hectare, which suggested that improvement can be achieved through simple selection. Bulb yield had significant and positive correlation with average bulb weight, equatorial diameter, plant height, polar diameter, days to harvest and days to 50% neck fall. Path analysis showed that bulb weight, equatorial diameter, bulb shape index, neck thickness, total soluble solids, plant height and leaf length had a positive direct effect on bulb yield.